2003
DOI: 10.1111/j.1553-2712.2003.tb01348.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Emergency Department Patients and Visitors Regarding Emergency Exception from Informed Consent in Resuscitation Research, Community Consultation, and Public Notification

Abstract: Objective: To assess public views on emergency exception to informed consent in resuscitation research, public awareness of such studies, and effective methods of community consultation and public notification. Methods: A face-to-face survey was conducted in two academic Level I trauma center emergency departments (EDs) in Oregon and Minnesota from June through August 2001. Results: Five hundred thirty people completed the survey, with an 82% response rate. The mean age of the respondents was 41 years (range 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 21 publications
4
59
0
1
Order By: Relevance
“…Our survey was modeled after one of the largest, and used similar questions for comparison (18). We found that 98% of our subjects agreed that emergency research is important, compared with 50% in that population (18). In that study, 34% of subjects felt that research without consent was justifiable in some circumstances, whereas 42% of ours felt that way.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Our survey was modeled after one of the largest, and used similar questions for comparison (18). We found that 98% of our subjects agreed that emergency research is important, compared with 50% in that population (18). In that study, 34% of subjects felt that research without consent was justifiable in some circumstances, whereas 42% of ours felt that way.…”
Section: Discussionmentioning
confidence: 74%
“…A number of other surveys have examined public opinion on this issue. Our survey was modeled after one of the largest, and used similar questions for comparison (18). We found that 98% of our subjects agreed that emergency research is important, compared with 50% in that population (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If there is full public information about what surveillance is being done, as well as oversight through the political process, then the political process might be viewed as analogous to community consent of the form utilized in research when subjects cannot be identified in advance (McClure et al 2003). However, it is important to note that so-called "community consent" models as they are currently implemented may fail to communicate adequately with community members about planned research.…”
Section: Syndromic Surveillance and The Patient As Victim And Vectormentioning
confidence: 99%
“…The purpose of community consultation is to ensure that the research is respectful of the community in which it is conducted and as such, understanding community perceptions and opinions of the research is paramount [7,8]. While many studies have been conducted regarding patient opinions of EFIC research, including patients being evaluated in the emergency department [8,9,10,11,12], stroke patients have largely been excluded from these studies since most are cognitively impaired upon arrival in the emergency department. Also, few of these studies explored the impact of varying levels of invasiveness of the proposed research.…”
Section: Introductionmentioning
confidence: 99%